Book Reviews - KS, (Kurdish Studies, 2022)
Khanna Omarkhali, The Yezidi Religious Textual Tradition: From Oral to Written. Categories, Transmission, Scripturalisation and Canonisation of the Yezidi Oral Religious Texts, Wiesbaden: Harrassowitz, 2017, 625 pp. (ISBN 9783447108560). Parvin Mahmoudveysi, Denise Bailey, Ludwig Paul, and Geoffrey Haig, The Gorani Language of Gawraǰū, a Village of West Iran: Texts, Grammar, and Lexicon, 2012, Wiesbaden: Reichert Verlag, 276 pp., (ISBN: 9783895008559). Mahmoudveysi, Parvin, and Denise Bailey. The Gorani Language of Zarda, a Village of West Iran: Texts, Grammar, and Lexicon, 2013, Wiesbaden: Reichert Verlag, 240 pp., (ISBN: 9783895009525). David Gaunt, Naures Atto, and Soner O. Barthoma, Let Them Not Return: Sayfo – The Genocide against the Assyrian, Syriac and Chaldean Christians in the Ottoman Empire, New York, Oxford: Berghahn Books, 2017, 274 pp., (ISBN: 97817853349869). Ahmed Fawaz, Opportunity, Identity, and Resources in Ethnic Mobilization: The Iraqi Kurds and the Abkhaz of Georgia, Lanham, Maryland: Lexington Books, 2017, 229 pp., (ISBN: 9781498534000). Michael M. Gunter (ed.), Kurdish Issues: Essays in Honor of Robert Olson, 2016, Costa Mesa, CA: Mazda Publishing, (ISBN: 9781568593104).